Impact of workplace displacement during a natural disaster on computer performance metrics: A 2-year interrupted time series analysis. - Sarnosky, Kamrie; Benden, Mark; Sansom, Garett; Cizmas, Leslie; Regan, Annette K.; Davis, Kermit; Kotowski, Susan (Work, 2022)
BACKGROUND: Remote working may enhance company resiliency during natural disasters and other events causing workplace displacement. OBJECTIVE: We conducted an interrupted time series analysis to investigate the impact of Hurricane Harvey on employee computer use during and after a seven-month displacement period from the physical workplace. METHODS: Ergonomic software was used to collect information on employees' computer usage. RESULTS: Although there was no change in total computer use in response to the hurricane (β 0.25), active computer use significantly declined (β –0.90). All measured computer use behaviors returned to baseline prior to the complete return to the physical workspace. CONCLUSION: Despite a transient period of reduced activity during closure of the workplace building, productivity returned to normal prior to the employees' return to a commercial workspace. The ability to work remotely may improve resiliency of employees to perform workplace tasks during events causing workplace displacement.